IDENTIFIKASI KADAR HEMOGLOBIN DARAH KAMBING PERANAKAN ETAWAH BETINA DALAM KEADAAN BIRAHI - I Gede Putu Kasthama; Eko Marhaeniyanto (BUANA SAINS, 2006)
This research was conducted at Field Laboratory of Animal Husbandry Tribhuwana Tunggadewi University. The aim of this research was to identify the hemoglobin level of female Etawah crossbreed goat in estrus phase. Ten female Etawah crossbreed goats with live weight 40,05  2,67 kg were used in this research 5 kg King Grass and 0,8 kg concentrate were given a day during the research. For estrus synchronization, it was used double injection of PGF2 with interval 11 days. Method used in this research was a case study with purposive sampling. Parameters measured in this research were: 1) hemoglobin level, 2) sign of estrus, 3) estrus cycle. The result of this research showed that female Etawah crossbreed with hemoglobin level 11,30 – 12,20 gm/100 ml in blood had good performance in estrus with normal estrus cycle